Procurement Digitalization With Odoo ERP: An Indonesian Airline Case Study - Nabila Qurrotu Aini; Siti Nursyamsiyah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the procurement business process of a private airline company in Indonesia, evaluate the effectiveness of the Odoo ERP system in supporting procurement activities, and identify the challenges encountered during its implementation. A descriptive qualitative case study approach was employed. Data were collected through semi-structured interviews, participant observation, and document analysis involving personnel directly engaged in procurement activities. The data were analyzed using thematic analysis. The findings indicate that Odoo ERP has improved procurement administration, document management, transparency, and data accuracy while facilitating procurement monitoring through a centralized database. However, the implementation remains partially constrained by manual procedures, incomplete cross-departmental integration, and occasional technical issues. The study highlights that the effectiveness of procurement digitalization depends not only on technological capabilities but also on organizational readiness and system integration. By providing evidence from the airline industry in Indonesia, this study contributes to the growing literature on ERP-enabled procurement digitalization and offers practical insights for organizations seeking to enhance procurement performance through integrated information systems.